Corporate Culture In The Organization: The Impacts Of Involvement Culture On Business Sustainability And Organizational Performance - Farah Laili Muda @ Ismail; Anita Ismail (Academic International Dialogue (AID) Academy, 2024)
The purpose of this study is to look at impacts of one of the types of corporate cultures in organization, that is involvement culture. In ensuring the viability of a business organization in the industry, there is no doubt that corporate culture plays an important role. Whether the culture comes from outside or sown from within the organization, it is found that corporate culture can boost the performance of an organization. Through a strong corporate culture, employees will better understand and conform to the work culture and at the same time be able to ensure a good and equal work output. This research paper is written through a thorough study on literatures. The types of corporate culture can be seen from the four main aspects emphasized by an organization such as the emphasis on adaptation to the environment, organizational achievement, employee involvement and consistency practices. This conceptual paper focuses on involvement culture as it is one of the cultures that has a strong influence on the performance of an organization. The findings of many studies show that involvement culture in the organization has positive impacts on business sustainability and organizational performance. This paper highlights the benefits of an involvement culture and may bring managers to be open-minded in empowering the employees and letting them make decisions in the organization.